2016
DOI: 10.1007/s00264-016-3192-5
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized study comparing results of fixation for clavicular shaft fractures with intramedullary nail or locking compression plate

Abstract: Minimal invasive intramedullary implantation technique provided satisfactory clinical outcomes and shortened the time until bony union compared to LCP fixation. Further study on larger populations is required to establish whether the technique offers lower complication rates than LCP fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…The data were collected through electronic chart reviews of patients who experienced displaced midshaft clavicle fractures and came to our institution for help and follow-up between April 2014 and December 2016. The inclusion criteria were as follows: (1) having a displaced middle-third clavicle fracture (Robinson type 2B1/2B2) [ 10 ], (2) age between 30 and 65 years, and (3) having a complete record of radiographic and functional evaluations at regular follow-up periods of at least 6 months. The exclusion criteria were as follows: (1) bilateral clavicle fracture, (2) fracture associated with other fractures or major injuries, (3) another trauma at the time of follow-up, and (4) initial injury combined with injured skin integrity or skin tenting of the fracture fragment.…”
Section: Aterials and Methodsmentioning
confidence: 99%
“…The data were collected through electronic chart reviews of patients who experienced displaced midshaft clavicle fractures and came to our institution for help and follow-up between April 2014 and December 2016. The inclusion criteria were as follows: (1) having a displaced middle-third clavicle fracture (Robinson type 2B1/2B2) [ 10 ], (2) age between 30 and 65 years, and (3) having a complete record of radiographic and functional evaluations at regular follow-up periods of at least 6 months. The exclusion criteria were as follows: (1) bilateral clavicle fracture, (2) fracture associated with other fractures or major injuries, (3) another trauma at the time of follow-up, and (4) initial injury combined with injured skin integrity or skin tenting of the fracture fragment.…”
Section: Aterials and Methodsmentioning
confidence: 99%
“…From these, 9 studies were excluded, including 4 that were quasi-randomized studies utilizing an alternate/odds-even method for randomization ( 20-23 ), 3 that were non-randomized studies ( 21 , 24 , 25 ), 1 that was a combined prospective and retrospective study ( 26 ) and 1 study ( 27 ) that was a long-term follow-up of a previously published trial (duplicate data). A total of 10 RCTs were finally included in the present systematic review and meta-analysis ( 14 , 15 , 28-35 ).…”
Section: Resultsmentioning
confidence: 99%
“…The sample size varied from 15-63 patients per group. The type of plate fixation used was different across studies: Titanium elastic nail was the choice of intramedullary fixation in 7 studies ( 15 , 28-30 , 32 , 33 , 35 ), while 2 utilized a Sonoma CRx Collarbone pin (Sonoma) ( 14 , 31 ) and 1 trial reported on the use of the Rookwood pin ( 34 ). Post-operative data were obtained after a follow-up of 12 months in the majority of studies, while 1 study reported follow-up data at 6 months ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations